Financial stability and climate change - Nikola Fabris (Journal of Central Banking Theory and Practice, 2020)
Fighting climate change is one of the biggest challenges in the 21st century. Climate change that leads to global warming has been increasingly visible in our environment. Extreme weather conditions such as hurricanes, floods, and droughts have been escalating and their acceleration can be expected in the future. They cause changes in sea levels, epidemics, large fires, etc. Increasingly, we are witnessing minor or major damage caused by these extreme weather conditions. Numerous studies have proven that climate change has negative impact on economic growth and prosperity. However, this paper starts from the premise that in addition to unequivocally identified threats, climate change also creates opportunities. The paper reaches a conclusion that climate change can adversely affect balance sheets of financial institutions. Therefore, climate change is a source of financial risk and thus a part of the mandate of central banks and supervisors in preserving financial stability. This type of risk has not been given enough attention by either supervisors or financial institutions over the past period. This paper develops a model for managing financial risks as a result of climate change.
Keywords: Q54; E58; 330; climate change; financial stability; financial risks; management